The effectiveness of some electronic evaluation tools in the development of the performance of computer teachers in the preparatory stage - Bassiouni, Rifat; Mohamed, Ahmed; Abdul Hamid, Abdul Aziz Tulbah (Arab Journal for Sciences and Research Publishing, 2016)
The current research aims to identify the effectiveness of suggested program for training by the internet, in order to make the teachers of computer at Kafrelsheikh Governorate gain the skills of design and produce the electronic performance also, develop their tendencies towards it. The researcher used the descriptive method and quasi experimental method. The experiment has been conducted on a sample of (30) teachers. The researcher used several research tools, like: identification card for the training needs of teachers- the cognitive achievement test which is related to skills – card for noticing the performance rate for skills of designing and producing achievement file electronically- evaluation card of electronic achievement file After the application of the program on the sample and the pre- and post-application of research tools, we reached The most important results is that  the training program based on the Internet has made effectiveness by (Makjoggion = < 0.6 ) at the aspects (skills and achievement). The training program based on the Internet has also achieved effectiveness in evaluating the performance of the computer teachers for the electronic achievement file, and the whole sample of research has perfected the production of the electronic achievement file.
Keywords: electronic calendar; performance development; computer teachers